Projections of Land-Cover Change in a Tropical High-Andean Lake - Madroñero Palacios, Sandra Milena; Muñoz Guerrero, Diego Andrés (Salehan Institute of Higher Education, 2025)
Land use and land cover change is one of the main drivers transforming high Andean ecosystems in Colombia. This study examines the spatial dynamics of land use in the La Cocha Ramsar Wetland between 1989 and 2020 and projects land cover scenarios to the year 2050 using spatial modeling techniques. Land cover maps for 1989 and 2020 were developed using satellite imagery and photo-interpretation, following the CORINE Land Cover methodology adapted for Colombia. A transition matrix and change indicators defined by the Institute of Hydrology, Meteorology and Environmental Studies (IDEAM) were used for multitemporal analysis, allowing the identification of processes such as forest fragmentation and recovery, agricultural expansion, and the spread of pastures. Future projections were modeled with the Land Change Modeler (LCM) module in the IDRISI Selva software, incorporating biophysical and socioeconomic variables with significant association (Cramér’s V > 0.4). Eight dominant transitions were identified, and change potential maps were generated. The model was validated through random field sampling and a confusion matrix analysis, yielding a Kappa index of 0.76, indicating strong agreement between simulated and observed data. Results show that 91.06% of the area remained unchanged, while 8.94% underwent transformations attributed to human activities. A net increase of 66.75 ha in dense forest is projected by 2050, along with growth in fragmented forest areas and agro-pastoral mosaics.